Estimation of NLRP3 Inflammasome Role and some Biochemical Parameters in Patients with Chronic Kidney Diseases (CKD) - Nada Hussain Alwan; Faraj, Hadeel (University of Thi-Qar Journal of Science, 2023)
Chronic kidney disease (CKD) is a widespread condition that poses a major threat to human health. With substantial public health costs, severe morbidity, and mortality, CKD prevalence is increasing. The study aimed to look at NLRP3 inflammasome , hsCRP , Urea , Creatinine, Uric acid and GFR levels. Serum NLRP3 inflammasome , hsCRP , Urea , Creatinine, Uric acid and GFR levels were determined in 90 patients with Chronic Kidney Diseases (CKD) , and 85 healthy subjects, an age range (30-75). The results of current study show a significant increase in the concentration of serum NLRP3 inflammasome, hs-CRP, urea , creatinine and uric acid in (CKD) patients group in comparison with controls group (p<0.05). While shows a significant decrease in GRF in (CKD) patients group in comparison with controls group (p<0.05). The aim of this study is estimated the NLRP3 inflammasome , Inflammation marker , kidney function tests and Glomerular filtration rate (GFR) in patients with Chronic Kidney Disease.